Transformation of cubic AgBiS 2 from nanoparticles to nanostructured flowers by a microwave-refluxing method - Tipcompor N. (2014)
Cubic AgBiS 2 nanoparticles and flower-like clusters were successfully synthesized by microwave refluxing of CH 3COOAg, Bi(NO 3) 3·5H 2O and thiosemicarbazide (NH 2NHCSNH 2) in ethylene glycol. The phase was detected by X-ray diffraction (XRD) and selected area electron diffraction (SAED). The SAED pattern was also in accordance with that of the simulation. Scanning and transmission electron microscopy (SEM and TEM) revealed the gradual transformation of nanoparticles into flower-like clusters by increasing microwave power. Their UV-visible absorption and photoluminescence (PL) emission were detected by spectrometry. Possible formation mechanism of nanoparticles and nanostructured flowers was also proposed according to the experimental results. © 2012 Elsevier Ltd and Techna Group S.r.l.